The Use of a Functional Behavioral Assessment-Based Self Management Intervention for Students with Emotional/Behavioral Disorders - Rasheed, Saleem A.; Fore, Cecil; Jones, Arthur; Smith, Latisha (Journal of the American Academy of Special Education Professionals, 2012)
The research literature on the use of Functional Behavioral Assessments (FBA) to develop Behavior Intervention Plans (BIP) for students with emotional/behavioral disorders, who present problem classroom behaviors for use in the schools, is well documented. There are school-wide, district-wide, and state-wide plans that are currently being implemented to satisfy the requirements imposed by IDEA (2004). The results from this study indicate that both participants experienced a significant reduction in their problem behaviors. The FBA-based self-management intervention procedure was both less intrusive on the teacher’s instructional time and effective, and can easily be incorporated into a student’s BIP.